TRANSCENDENT JUSTICE? LEGAL AND PHILOSOPHICAL PERSPECTIVES - Ion COPOERU; Andrea-Annamaria CHIŞ (Studia Universitatis Babeș-Bolyai. Philosophia)
In this paper, we shall use the perspectival view on justice in an attempt to accommodate the transcendent view on justice with the adversarial practice of justice. Its main idea is that, before seeing justice as administration, it has to be seen in itself. The first section of the paper discusses the meaning of justice from a phenomenological point of view, which enables us to envision justice as transcendent. The second section of the paper describes the pluri-perspectivism of law and justice on the procedural level. Through a series of reflections upon the procedural aspects as they are operating in the Romanian judiciary, we show how the plurality of perspectives tends to converge and finds its resolution in the rule of law and Modern democracy.